Methodology Of Presentation Of Educational Materials For The Development Of Electronic Information Educational Resources (Eurasian Research Bulletin, 2022)
This article focuses on issues related to the provision of training material for the development of electronic information educational resources, which are rarely studied by students of university. The relevance and professionalism of the information included in the article will allow to solve a number of problems more effectively, and will also help to increase the level of presentation of training material, which is traditionally engaged in assisting in these matters.